2021
DOI: 10.1021/acsaelm.0c00978
|View full text |Cite
|
Sign up to set email alerts
|

Strong Electronic Coupling of Graphene Nanoribbons onto Basal Plane of a Glassy Carbon Electrode

Abstract: The electrochemical behavior of graphene nanoribbons deposited onto glassy carbon electrode using pi-stacking interactions was investigated. We illustrate here that strong electronic communication could be achieved with basal plane of glassy carbon using simple electrochemical treatment. File list (3) download file view on ChemRxiv Manuscript.pdf (762.42 KiB) download file view on ChemRxiv Supporting_Information.pdf (2.07 MiB) download file view on ChemRxiv Manuscript.docx (49.18 MiB)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 50 publications
6
15
0
Order By: Relevance
“…The cathodic feature is chemically reversible and exhibits pronounced pH-dependence. Similar behavior was observed previously for bipyrimidine-based nanographenes, 33 and is assigned to a two-electron, two-proton reduction of the bpm moiety to the corresponding dihydro-bipyrimidine (bpmH2) analog (Scheme 1). The bpm reduction feature exhibits a modest current enhancement in the cathodic scan for CVs collected at pH<2.0 (observable in the pH=2 CV, Figure 1a).…”
Section: Resultssupporting
confidence: 84%
“…The cathodic feature is chemically reversible and exhibits pronounced pH-dependence. Similar behavior was observed previously for bipyrimidine-based nanographenes, 33 and is assigned to a two-electron, two-proton reduction of the bpm moiety to the corresponding dihydro-bipyrimidine (bpmH2) analog (Scheme 1). The bpm reduction feature exhibits a modest current enhancement in the cathodic scan for CVs collected at pH<2.0 (observable in the pH=2 CV, Figure 1a).…”
Section: Resultssupporting
confidence: 84%
“…In a previous electrochemical (non-photophysical) study, we showed that bipyrimidine units behave as redoxactive electron accepting moieties, undergoing efficient proton-coupled electron transfer processes. 36 In this study, we show that GQD and GNR exhibit excited states with chargetransfer character, where bipyrimidine units serve as electron acceptors, an important property for efficient photoinduced charge separation required in photocatalytic applications. Furthermore, we find that the edge chlorination has a beneficial effect on the excited-state lifetimes of GNRs, due to the significant reduction in the non-radiative decay pathways associated with -stacking between aromatic cores.…”
Section: Introductionmentioning
confidence: 76%
“…The polymerization of 3-Br via Yamamoto coupling yields polymer-3, which is then oxidized to H-GNR using FeCl3. The MS characterization of polymer-3 36 indicates that ribbons up to ~20 nm in length (~16 3H units) are formed, while longer polymer-3 units, which may exist in the H-GNR sample, are not expected to get ionized and detected in the mass spectrometry. The ICl chlorination methods yield Cl-GNR, which have been characterized using XPS and NMR (Section S1, SI).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has recently been shown that strong coupling between glassy carbon electrodes can be achieved through basal plane modification with nitrogen-doped GNRs. When the GNRs are determined to be in strong communication with the electrode surface, every ET across the entire pH region (0–14) was coupled to PT 99 . These results point to an important difference between homogeneous and heterogeneous catalysts: while isolated electron transfer events can take place in homogeneous catalysts, they are always coupled by a compensating transfer of charged groups, e.g., protons, in the case of heterogeneous catalysis.…”
Section: Insights From Molecular Modelsmentioning
confidence: 99%